If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 + 2x = 5x + -4 Reorder the terms: 3 + 6x + 2x = 5x + -4 Combine like terms: 6x + 2x = 8x 3 + 8x = 5x + -4 Reorder the terms: 3 + 8x = -4 + 5x Solving 3 + 8x = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + 8x + -5x = -4 + 5x + -5x Combine like terms: 8x + -5x = 3x 3 + 3x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + 3x = -4 + 0 3 + 3x = -4 Add '-3' to each side of the equation. 3 + -3 + 3x = -4 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = -4 + -3 3x = -4 + -3 Combine like terms: -4 + -3 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333
| -16k+7k=k-2k | | 7.2x-4.9=60.1 | | (32x^2-8x+4)=0 | | 3/7-3x | | (x+5)(x+2)=25 | | 5x^2+2Y^2+2xy-2x-4y+2=0 | | 4x+5+2x+12=180 | | 2x^2+5y^2=16 | | a^2+b^2=625 | | 7(z+3)-3z=44 | | 10+15y=3y | | Sin(3x)+sin(9x)= | | 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 | | 2(f-3)=f+5 | | 100=60a+[40(2a)] | | -9=x(-10/x) | | 18x+6x-4x+2=2x-10x+16 | | 5x+5=4y-23 | | 2/7*3/8 | | Y-2=5(x-1)/3 | | 18-2x=12-5x | | y+w=c | | x^4y^2-4x^2y=0 |